The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.3989/scimar.2003.67n3371
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability in voluntary dive duration of the Mediterranean loggerhead turtle, <i>Caretta caretta </i>

Abstract: SUMMARY:We characterised the effect of seasonal fluctuations in water temperature (T w ) on the nonventilatory period (NVP) of Mediterranean loggerhead turtles, Caretta caretta. Ten captive turtles, that were subject to the natural variations in T w found in the Gulf of Naples, dived significantly longer when T w decreased. More than 50% of summer and winter dives lasted between 2 and 10 min; the maximum dive duration (120 min) occurred in winter at a T w of 13°C. The longest NVP coincided with a low level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 14 publications
(15 reference statements)
1
11
0
Order By: Relevance
“…The lack of a capacity to compensate dive behaviour for seasonal thermal variability in A. arafurae is consistent with similar findings in freshwater crocodiles (Campbell et al 2010a, b) and some turtle species (e.g. Clark et al 2008b;Gordos et al 2003a;Bentivegna et al 2003) and suggests that in air-breathing diving ectotherms, dive behaviour especially in warm environments is not subject to thermal acclimation. Therefore, for air-breathing diving ectotherms like A. arafurae, future environmental warming could have substantial consequences for behaviour and in turn could result in reduced survivorship.…”
Section: Number Of Divessupporting
confidence: 77%
“…The lack of a capacity to compensate dive behaviour for seasonal thermal variability in A. arafurae is consistent with similar findings in freshwater crocodiles (Campbell et al 2010a, b) and some turtle species (e.g. Clark et al 2008b;Gordos et al 2003a;Bentivegna et al 2003) and suggests that in air-breathing diving ectotherms, dive behaviour especially in warm environments is not subject to thermal acclimation. Therefore, for air-breathing diving ectotherms like A. arafurae, future environmental warming could have substantial consequences for behaviour and in turn could result in reduced survivorship.…”
Section: Number Of Divessupporting
confidence: 77%
“…Marine pollution caused by persistent organic pollutants (POPs), and resultant diseases, human activities such as the development of tourism, coastal urbanization, and naval traffic, and particularly incidental fisheries capture are potential threats to the survival of Caretta caretta in the Mediterranean Sea (Laurent et al 1996, Bentivegna et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…This turtle began to breathe regularly 5 min after the start of the fat biopsy. Although this period of apnea appears prolonged, it was still well within the maximum dive durations of up to 2 hr (Bentivegna et al, 2003) and 7 hr (Hochscheid et al, 2005) reported for loggerheads in winter, and it is comparable to routine dive durations of subadult loggerheads of 19-30 min (Lutcavage and Lutz, 1997). The fact that all treatment turtles experienced apnea may be attributable to the method of i.v.…”
Section: Discussionmentioning
confidence: 80%